Pengaruh Pupuk Kompos Jerami Padi dan Kompos Titonia (Tithonia diversivolia) terhadap Pertumbuhan dan Hasil Tanaman Gandum (Triticum aestivum L.) Kultivar GURI 6 UNAND - Nunung Hidayaty; Irfan Suliansyah; Irawati Irawati (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2017)
The aim of this research were to find the best doses of rice straw and tithonia compost base on growth and yield of wheat plant. Experimen had been conducted in Alahan Panjang, Solok Regency from April untuk July 2016. It used Randomized Block Design (RBD) with 2 factor and 3 blocks. The firs factors were of rice straw compost with doses (0 ton/Ha, 5 ton/Ha, 10 ton/Ha and 20 ton/Ha) and second factor was were doses of tithonia compost (0 ton/Ha, 5 ton/Ha, 10 ton/Ha and 20 ton/Ha). Data were analyzed statistically by F test and when F calculated was greater than F table 5% continued with Tukey Test on the real level 5%. The result showed there was an interaction between rice straw and titonia compost to the leaf area indeks, net assimilation rate, crop growth rate, number of productive tillers, grain number, grain weight and grain yield. Rice straw compost with 10 ton/Ha dose gave best result on number of spikelet. Rice straw compost with dose 10 ton/Ha and titonia compost with dose 5 ton/Ha gave the best result on leaf area indeks, net assimilation rate, crop growth rate, number of productive tiller, grain number, grain weight and grain yield.